Pengaruh Kurs, Deposito Dan Bi Rate Terhadap Profiatbilitas Dengan Kredit Sebagai Variabel Mediasi ( Studi Empiris Pada Bank Umum Di Indonesia ) (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to analyze the effect of exchange rate, deposit and bi rate on profitability with credit as a mediating variable. The population in this study is all monthly data from the exchange rate, BI rate, deposits, credit and profitability (ROA) of conventional commercial banks in Indonesia. The sampling method is purposive sampling with the criteria used being the closest (up to date) period by taking available data from January 2011 to December 2021. The results of hypothesis testing show that hypothesis 1 (H1) that the exchange rate has a negative effect on credit is not proven and cannot be interpreted. Hypothesis 2 (H2) that deposits have a positive effect on credit is proven and can be interpreted that an increase in the amount of deposits will increase the amount of credit. Hypothesis 3 (H3) that the BI rate has a negative effect on credit is proven and can be interpreted that an increase will reduce the amount of credit. Hypothesis 5 (H5) that the exchange rate has a negative effect on profitability is proven and can be interpreted that an increase in the exchange rate will reduce ROA. Hypothesis 6 (H6) that the BI rate has a negative effect on ROA is not proven and cannot be interpreted. The hypothesis (H7) that exchange rates have an effect on ROA with credit as a mediating variable is not proven. Because the results of the hypothesis testing are not significant, there is no mediating effect. The hypothesis (H8) that the BI rate has an effect on ROA with credit as a mediating variable is proven, resulting in a mediating effect and it can be interpreted that an increase in the BI rate will decrease ROA.